2012
DOI: 10.1108/02652321211236914
|View full text |Cite
|
Sign up to set email alerts
|

Exploring customer switching intentions through relationship marketing paradigm

Abstract: PurposeThe purpose of this paper is to investigate the extent of customer switching and the reasons that underlie customer‐switching intentions. The paper aims to focus on the various factors on account of which a customer may or may not switch a particular bank.Design/methodology/approachA total of 800 bank customers were selected randomly from a total population of 71,600 and were contacted personally to gather the requisite data.FindingsThe paper finds that the model reveals significant effect of quality, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 109 publications
3
48
0
3
Order By: Relevance
“…In fact, as Kaur et al (2012) recently claimed, the nature and extent of switching behaviour in the banking sector has not been passably studied.…”
Section: The Research Gap and Research Modelmentioning
confidence: 96%
“…In fact, as Kaur et al (2012) recently claimed, the nature and extent of switching behaviour in the banking sector has not been passably studied.…”
Section: The Research Gap and Research Modelmentioning
confidence: 96%
“…The review of works carried out by (Berry, 2002;Gummesson, 2002;Juš ius, Navickas, and Jonikas, 2006;Lee and Jun, 2007;Bivainis, Daukševi i t , and Vilkait , 2011;Kaur, Sharma, and Mahajan, 2012) and other scientists revealed that creation, nurturance and fostering of long-term relationship is an underlying and broadly discussed issue; however, it should be highlighted that there has not been reached any united point of view concerning the customer retention.…”
Section: Introductionmentioning
confidence: 95%
“…Ladhari, Ladhari and Morales (2011) conceptualised loyalty as a customer's continued patronage of a particular bank. Underlining the role of satisfaction, Amin, Isa and Fontaine (2011) and Kaur, Sharma and Mahajan (2012) suggested that customers retort unfavourably and switch to other service providers upon experiencing dissatisfaction, thereby affecting customer loyalty negatively. Rai and Srivastava (2013) defined customer loyalty as a "psychological character formed by sustained satisfaction of the customer coupled with emotional attachment formed with the service provider that leads to a state of willingly and consistently being in the relationship with preference, patronage and premium".…”
Section: Customer Loyalty: Concept and Connotationmentioning
confidence: 97%